Associations de pays et production de locality : la « campagne Munzur » contre les barrages - Marie Le Ray (European Journal of Turkish Studies)
Taking the example of migrants coming from the Kurdish Alevi province of Tunceli (Eastern Turkey), this contribution analyses the phenomenon of hemşehri associations by looking at their ability to produce locality [Appadurai]. The paper aims to question the ways in which these associations (re)produce a sense of local belonging in the places of settlement. This local identity contributes to shape loyalties, attitudes and acts towards the migrants’ originating province, as well as within the area of settlement. Furthermore, the production of locality is a highly dynamic and conflicting process: other actors – including the state – promote, sometimes violently, their own sense of belonging and accompanying spatial beliefs. As a case in point, this paper makes a detailed examination of the campaign launched by the ‘Tuncelili associations’ in 1999 to prevent the state-sponsored construction of dams in the province’s Munzur valley. Special attention is given to the modification of the definition of local identity which results from mobilization against the state, and also from the complex articulation of spaces, both local and global.